Data Protection Impact Assessment Indicators in Protecting Consumer Personal Data on E-commerce Platforms - Tegar Islami Putra; Nurul Fibrianti; Mohammad Raziq Fakhrullah (The Indonesian Journal of International Clinical Legal Education, 2024)
Efforts to protect consumers' personal data on e-commerce platforms can be carried out by conducting a Data Protection Impact Assessment. This article discusses the indicators of the execution of Data Protection Impact Assessment by pivoting on the rights of personal data subjects based on Law Number 27 of 2022.  This research uses a library research method by focusing on legal materials so that it can be said to be library based. The results show that Data Protection Impact Assessment is explained in Article 34 paragraph (1) of Law Number 27 of 2022 concerning Personal Data Protection which is then further regulated through Government Regulations as mandated by Article 34 paragraph (3). However, the Government Regulation relating to this matter has not yet been ratified, so it still refers to the mandate of Law Number 27 of 2022. This Data Protection Impact Assessment indicator can refer to Article 16 paragraph (2), Article 34 paragraph (1) and (2), Article 35, Article 20 paragraph (2), and Article 27 of Law Number 27 Year 2022. In terms of Data Protection Impact Assessment indicators as the protection of consumer personal data on e-commerce platforms, it can refer to the mandate that explains the rights of personal data subjects and their limitations in a separate article and the form of personal data processing as mandated by Article 34 paragraph (2) of Law No. 27 of 2022.